1999
DOI: 10.1103/physrevb.60.12651
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure phase transition and properties of spinelZnMn2O4

Abstract: X-ray photoelectron spectroscopy, magnetic measurements, and a single-crystal x-ray structure determination at normal pressure have shown that Jahn-Teller active manganese ions in ZnMn 2 O 4 are present in one valence state ͑III͒ on the octahedral sites of the spinel structure. The high-pressure behavior of ZnMn 2 O 4 was investigated up to 52 GPa using the energy-dispersive x-ray diffraction technique and synchrotron radiation. The structural first-order phase transition from the body-centered to primitive-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 20 publications
5
71
1
Order By: Relevance
“…However, the theoretical study has suggested that a possible phase transition from the cubic spinel towards the tetragonal spinel structure can be explained by the presence of non-hydrostatic conditions. This transition had already been observed in ZnMn 2 O 4 [8] and NiMn 2 O 4 [9]. Figure 1 shows the unit cells of the cubic spinel, marokite, CaFe 2 O 4 and CaTi 2 O 4 phases.…”
Section: Introductionmentioning
confidence: 70%
“…However, the theoretical study has suggested that a possible phase transition from the cubic spinel towards the tetragonal spinel structure can be explained by the presence of non-hydrostatic conditions. This transition had already been observed in ZnMn 2 O 4 [8] and NiMn 2 O 4 [9]. Figure 1 shows the unit cells of the cubic spinel, marokite, CaFe 2 O 4 and CaTi 2 O 4 phases.…”
Section: Introductionmentioning
confidence: 70%
“…The simultaneous increase of the Zn x Mn 3ÿx O 4 phase and decrease of the ferromagnetic signal suggests that this phase is not responsible for the RT FM. Although there is some controversy about the magnetic properties of this spinel, it is well known that it exhibits paramagnetic behavior at RT [7]. For a further understanding, several samples in the Zn x Mn 3ÿx O 4 system have been prepared and characterized.…”
mentioning
confidence: 99%
“…• Li in spinel LiTiS 2 (linear MEP); 51,52 • Zn in spinel ZnMn 2 O 4 (linear MEP); 23,53 • Zn in post-spinel ZnMn 2 O 4 (linear MEP); 54 • Li in olivine LiFePO 4 (curved MEP); [55][56][57][58][59] • Mg in δ-MgV 2 O 5 (curved MEP); 25,26,60,61 • Ca in layered CaMoO 3 (curved MEP). 62 To quantify the accuracy of the PathFinder algorithm in reproducing the geometry of the fully converged MEP, we define an error metric, shown schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%